2016
DOI: 10.1139/cjas-2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin E supplementation on cholesterol, vitamin E content, and fatty acid profile in chicken muscles

Abstract: The aim of the study was to determine the effect of dietary vitamin E level on cholesterol and vitamin E content and fatty acid profile in broiler chicken breast and leg muscles. Chickens (420 cocks) were randomly divided into two feeding groups (210 birds each). The control group was fed with standard diet containing 44 mg kg −1 of vitamin E, whereas the experimental group was supplemented with extra 200 mg kg −1 of vitamin E. The dietary addition of vitamin E caused a significant increase in its content in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…Atherogenic index (AI) and thrombogenic index (TI) are based on the FA profile and indicate the risk of atherosclerosis and thrombotic diseases emergence related to consumption of food products characterised by them. In dried jerky ostrich and chicken meat, these indexes were on a very low level compared to beef meat ( Table 5 ), as has been confirmed by previous studies on raw meat [ 40 ].…”
Section: Resultssupporting
confidence: 79%
“…Atherogenic index (AI) and thrombogenic index (TI) are based on the FA profile and indicate the risk of atherosclerosis and thrombotic diseases emergence related to consumption of food products characterised by them. In dried jerky ostrich and chicken meat, these indexes were on a very low level compared to beef meat ( Table 5 ), as has been confirmed by previous studies on raw meat [ 40 ].…”
Section: Resultssupporting
confidence: 79%
“…Thus, in the present study we found that both hesperidin and naringin had significant and dose-dependent beneficial effects on various factors of fat quality related to human health, mainly in the breast muscle and fat pad. Consistently with previous reports, many of these effects were also observed following vitamin E supplementation [ 38 , 39 ], but they were more pronounced in the case of the two flavanones.…”
Section: Discussionsupporting
confidence: 92%
“…Our results regarding serum total cholesterol levels confirmed that dietary garlic products reduced the blood cholesterol level in broilers (Choi et al, 2010;Moradi et al, 2013). This may be explained by the fact that garlic is effective in the regulation of lipid and cholesterol metabolism (Karim et al, 2017), similarly to the effect of dietary vitamin E (Zdanowska-Sąsiadek et al, 2016). The increase in both FI and BW gain in FGE fed birds may be attributed to FGE's growth promoting effects and antioxidant and hypocholesterolemic activities in the regulation of lipid metabolism (Choi et al, 2010) and to a lowering of the animal's physiological and metabolic stress, by contributing to animal welfare (Kim et al, 2009).…”
Section: Discussionsupporting
confidence: 79%